Synergistic activation of NF-κB by nontypeable Haemophilus influenzae and tumor necrosis factor α - Watanabe, Takahiro (National Academy of Sciences, 2004)
Nontypeable Haemophilus influenzae (NTHi) is an important human pathogen causing otitis media in children and exacerbation of chronic obstructive pulmonary disease in adults. Like most other bacterial infections, NTHi infections are also characterized by inflammation, which is mainly mediated by cytokines and chemokines such as tumor necrosis factor α (TNF-α). Among a variety of transcription regulators, NF-κB has been shown to play a critical role in regulating the expression of large numbers of genes encoding inflammatory mediators. In review of the current studies on NF-κB regulation, most of them have focused on investigating how NF-κB is activated by a single inducer at a time. However, in bacteria-induced inflammation in vivo, multiple inducers including both exogenous and endogenous mediators are present simultaneously. A key issue that has yet to be addressed is whether the exogenous inducers such as NTHi and the endogenous factors such as TNF-α activate NF-κB in a synergistic manner. We show that NTHi and TNF-α, when present together, synergistically induce NF-κB activation via two distinct signaling pathways: NF-κB translocation-dependent and -independent pathways. The NF-κB translocation-dependent pathway involves NF-κB-inducing kinase-IκB kinase β/γ-dependent phosphorylation and degradation of IκBα, whereas the NF-κB translocation-independent pathway involves mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase kinase kinase 1-dependent activation of MAPK kinase 3/6-p38 MAPK pathway. In addition, the same signaling pathways are also involved in synergistic induction of TNF-α, IL-1β, and IL-8. These studies should deepen our understanding of the molecular mechanisms underlying the combinatorial regulation of inflammation and lead to development of therapeutic strategies for NTHi-induced infections.